IDENTIFIKASI RHODAMIN B PADA KERUPUK MERAH YANG BEREDAR DI PASAR TRADISIONAL KOTA ENDE, PROVINSI NUSA TENGGARA TIMUR - Agustina Mogi; Mathildis Natalia Ga’a (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Crackers are popular dry snacks made from starch-based ingredients. However, some colored crackers are suspected to contain illegal dyes like rhodamine B, which is commonly used in the textile industry. Consumption of rhodamine B can cause health issues, including poisoning and cancer. This study aims to detect rhodamine B in red crackers sold at Mbonggawani, Potulando, and Wolowona markets. The method used is Thin Layer Chromatography (TLC) with a solvent mixture of ethyl acetate, n-butanol, and ammonia (20:55:25). Out of the three samples tested, one sample tested positive for rhodamine B, indicated by a pink spot that fluoresces yellow under UV light at 254 nm. The Rf value of the sample was 0.7, consistent with the standard rhodamine B range (0.2–0.8).